Liver Transplantation for Acute Liver Failure due to Mushroom Poisoning - Canbaz, Hayri; Bestemir, Attila; Akbulut, Sami; Yilmaz, Sezai; Yavuz, Yusuf (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Liver transplantation is a life-saving approach in some cases of mushroom poisoning, which is one of the important causes of acute liver failure. However, debate continues regarding the timing of liver transplantation. The aim of this study is to retrospectively evaluate the results of patients who underwent liver transplantation due to mushroom poisoning. Materials and Methods: In this descriptive and observational study, the demographic and clinical data of 26 patients who presented to emergency units due to clinical features of acute hepatic failure secondary to mushroom poisoning between October 2008 and November 2023 and who underwent emergent liver transplantation were retrospectively reviewed. Results: A total of 26 patients with a median (IQR) age of 39 (36) years were included in this study. The patients were divided into two groups: alive (n = 18) and dead (n = 8). No statistically significant differences were found between groups in terms of age, BMI, blood groups, hepatic encephalopathy grade, biochemical analysis obtained on the first days of hospital admission (AST, ALT, creatinine, ammonia, PTT, INR, albumin, platelets, HGB), ICU stay, cold ischemia time (CIT) and warm ischemia time (WIT), total bilirubin (P = .052), and time from poisoning to admission (P = .051). On the other hand, there were statistically significant differences between the alive and dead groups in terms of MELD score (P = .016; 23 vs. 34), re-transplantation (P = .022; 0% vs. 37.5%), hospital stay (P = .004; 24 vs. 6 days), and follow up (P < .001; 3423 vs. 5 days). Conclusions: This study showed that mortality was higher in patients with high MELD scores and patients who underwent re-transplantation. However, this study needs to be supported by multicenter prospective studies. Cite this article as: Canbaz H, Bestemir A, Akbulut S, Yilmaz S, Yavuz Y. Liver transplantation for acute liver failure due to mushroom poisoning. Turk J Gastroenterol. 2025;36(2):107-113.